Investigating The Properties Of Selected Natural Fiber And The Wound Care Performance Of Developed Diabetic Shoe Insole - Malathy, R.; Devi, R. Geetha (Journal of Neonatal Surgery, 2025)
The textile industry taps into recent science and technological developments to meet the ever-increasing consumer interest. The applications of textiles are not just limited to regular apparel and home textiles but expand much now on functional applications recognized under the technical textiles globally. Among the various categories of technical textiles, medical textile has played a vital role in addressing various needs of practitioners and patients. Treatment for diabetic wounds still remains challenge in the medical industry. Therefore, it is need of the hour to develop a non-woven composite diabetic insole using natural fiber. This paper is about the research of natural fibers and their properties, with their benefits to prepare nonwoven shoe insoles for diabetic foot Ulcers. Natural fiber nonwoven diabetic insoles have been produced and assessed for their wound healing capabilities. Four fibers were selected to construct a nonwoven composite. Extracted Fiber and developed nonwoven composites was evaluated for its FTIR, SEM analysis and wound healing property